Peningkatan Tanggung Jawab Siswa dalam Kerja Kelompok Melalui Model Pembelajaran Quantum Learning Berbasis Multiple Intelligences di SMP Negeri 23 Bandung - Hari Rudiana; Muhammad Andriansyah Purba; Yadi Budiman; Lili Halimah (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service program aimed to improve students’ sense of responsibility in group work through the implementation of a Quantum Learning model integrated with Multiple Intelligences (MI) at SMP Negeri 23 Bandung. The background of this initiative lies in the low levels of active participation and responsibility among students during group learning activities in Social Studies (IPS) classes. The target audience included ninth-grade students and Social Studies teachers. The activities involved teacher training, classroom facilitation, and direct observation of students’ collaborative behavior. Data were collected through observation, interviews, documentation, and MI questionnaires, then analyzed thematically. The results showed a significant improvement in students’ responsible behavior, demonstrated by timely task completion, active contributions, and self-reflection on group roles. In addition, Social Studies teachers enhanced their capacity to apply adaptive learning approaches that accommodate students’ diverse intelligences. This program had a positive impact on fostering a collaborative learning culture that supports the unique potential of each learner.